Expression profiles of Cry1Ab protein and its insecticidal efficacy against the invasive fall armyworm for Chinese domestic GM maize DBN9936 - Jin-gang LIANG; Dan-dan ZHANG; Dong-yang LI; Sheng-yuan ZHAO; Chen-yao WANG; Yu-tao XIAO; Dong XU; Yi-zhong YANG; Guo-ping LI; Li-li WANG; Yu GAO; Xue-qing YANG; et al. (Journal of Integrative Agriculture)
The fall armyworm (FAW) Spodoptera frugiperda, which originated in the Americas, is advancing across China and threatening the nation's maize crops. Currently, one widely used tool for its control is genetically modified (GM) Bacillus thuringiensis (Bt) maize. Sufficient content of Bt protein in appropriate plant parts is crucial for enhancing resistance against insect pests. In this study, we conducted a systematic investigation of Cry1Ab levels in Chinese domestic GM maize DBN9936, which has recently obtained a biosafety certificate, and evaluated its efficacy against FAW. Quantification of expression levels of Cry1Ab, via ELISA, indicated a spatio-temporal dynamic, with significant variation of mean Cry1Ab, ranging from 0.76 to 8.48 μg g−1 FW with the Cry1Ab protein level ranked as: V6–V8 leaf>R1 leaf>R4 leaf>R1 silk>VT tassel>R4 kernel. Among the nine locations, the Cry1Ab levels in DBN9936 of the Xinxiang, Langfang, and Harbin fields were significantly lower than those from Wuhan and Shenyang, and were slightly, but not significantly lower than those from the other four fields. Furthermore, the artificial diet–Cry1Ab mixture and plant tissue feeding bioassays revealed that DBN9936 has high efficacy against FAW. The insecticidal efficacy of different tissues against FAW larvae reached 34–100% with a descending order of lethality as follows: VT leaf>R4 leaf>R1 husk>R1 silk>VT tassel>R4 kernel. Taken together, our results showed that Bt-Cry1Ab maize DBN9936 has potential as a promising strategy to manage FAW.